2008
DOI: 10.1152/ajpheart.00151.2008
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite reductase activity of hemoglobin as a systemic nitric oxide generator mechanism to detoxify plasma hemoglobin produced during hemolysis

Abstract: Hemoglobin (Hb) potently inactivates the nitric oxide (NO) radical via a dioxygenation reaction forming nitrate (NO(3)(-)). This inactivation produces endothelial dysfunction during hemolytic conditions and may contribute to the vascular complications of Hb-based blood substitutes. Hb also functions as a nitrite (NO(2)(-)) reductase, converting nitrite into NO as it deoxygenates. We hypothesized that during intravascular hemolysis, nitrite infusions would limit the vasoconstrictive properties of plasma Hb. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 87 publications
1
41
1
Order By: Relevance
“…We also find a correlation between nitrite reductase activity and the protein's oxygen binding properties (P 50 and n 50 ) and this may play a significant role in making these materials non-vasoactive (60). The circulatory site at which the protein's nitrite reductase activity is maximal correlates with the deoxygenation of the protein (P 50 ) (64,90). BT-Hb and BT-PEG are expected to produce NO at physiologically relevant sites with low pO 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also find a correlation between nitrite reductase activity and the protein's oxygen binding properties (P 50 and n 50 ) and this may play a significant role in making these materials non-vasoactive (60). The circulatory site at which the protein's nitrite reductase activity is maximal correlates with the deoxygenation of the protein (P 50 ) (64,90). BT-Hb and BT-PEG are expected to produce NO at physiologically relevant sites with low pO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The site at which the rate of NO production is fastest depends directly on the HBOC's P 50 (64,90). BT-Hb and BT-PEG both have high oxygen affinities (P 50 = 9.3 and 4.1 respectively).…”
Section: Nitrite Reductase Activity At Physiologically Relevant Sitesmentioning
confidence: 99%
“…10,14 Systemic infusions of nitrite in dogs exhibit both arteriolar and venous dilation, with more potent effects on the systemic vascular resistance, increasing cardiac output. 15 Numerous normal human volunteer studies have now demonstrated that nitrate supplementation can increase exercise efficiency, as defined by total oxygen consumption (V ⋅ o 2 ) for total work performed (Watts). 11 In preclinical studies, nitrite has been shown to exhibit therapeutic efficacy in mouse, rat, and sheep models of pulmonary hypertension and mouse models of heart failure.…”
Section: Articles See P 371 and P 381mentioning
confidence: 99%
“…Although only deoxy heme catalyzes the reaction, O 2 tensions that half-saturate Hb maximize the release of NO-equivalents to the vasculature, as evidenced by nitrite-induced vasorelaxation (49,53,75). This has been attributed to the redox potential shift associated with formation of some R-state Hb as O 2 is bound (49,53,75). However, it is more appropriately ascribed to a shift in kinetics of the reaction than to the redox potential, which specifies the thermodynamic driving potential for heme oxidation/reduction and does not define the reaction rate (see Thermodynamic and kinetic aspects of Hb oxidation section).…”
Section: Redox Reactions Of Hb With Nitritementioning
confidence: 99%
“…Specifically, NO-dependent reactions involving formation of SNO-Hb have been shown to be under the control of allosteric reactions that alter the reactivity of b93Cys (8,65). In addition, in the presence of nitrite, Hb functions as an allosteric nitrite reductase, with maximal NO generation around the intrinsic oxygen affinity (P 50 ) of Hb, suggestive of allosteric controls of this reaction (75). It is by virtue of the differences in reactivity of Hb's R-and T-states that its reactions with nitrites and/or formation of SNO-Hb have been proposed to have specific therapeutic application during intravascular hemolysis and during administration of Hb-based blood substitutes, or even as means of reversing of storage-induced alterations in the properties of red blood cells (75).…”
Section: Redox Properties Of Structurally Diverse Hbsmentioning
confidence: 99%